Aplikasi Sistem Informasi Geografis Untuk Analisa Tata Ruang Wilayah Kabupaten Lamongan - Fauzi, Akhmad (JURNAL TEKMAPRO, 2008)
Abstract : The existing lamongan Sub-Province is executing autonomy Daerah, so request of information about development of area lamongan hardly is required. But constraint faced is gathering of the information from various sectors relating to geographical position from it area . so consequence triggers to give complete presentation of geographical information , accurate and safe. Hence its the solution is with making geospatial information system, which is aliance data at map and its(the information), information consisted of form database, tables, data thematic at map and photo. By Using SIG to assists Local Government Lamongan in planning of area as according to information to phase here in after. Keywords : Geospatial Information System (GIS), regional planology , geographical information